Mixing Rule of Sanches-Lacombe Equation of State for Prediction of Solvent Solubility in Polymer Solution - Wibawa, Gede (IPTEK The Journal for Technology and Science, 2008)
In this work, mixing rule of Sanches-Lacombe equation of state (SL-EoS) was developed for estimating vapor-liquid equilibria of solvent-polymer systems or solubility of solvent in polymer solutions. The model was derived by matching excess Gibbs energy of Sanches-Lacombe equation of state and that of group contribution model at zero pressure. Present model can be applied to wide range of pressure. In addition, this model covers systems with various molecular interactions, since functional group interaction parameters of UNIFAC-FV and UNIFAC-ZM models have been available for various groups.